2015
DOI: 10.1590/1516-3180.2015.00171105
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between genotype, psychiatric symptoms and quality of life in adult patients with sickle cell disease in São Paulo, Brazil: a cross-sectional study

Abstract: A relação entre genótipo, sintomas psiquiátricos e qualidade de vida em pacientes adultos com doença falciforme em São Paulo, Brasil: um estudo transversal ) showed lower scores for the "general health" and "role-physical" HRQoL domains, without interference from psychiatric symptoms. In the "role-physical" domain, the more severe genotype operated as a protective factor for HRQoL (β = 0.255; P = 0.007). CONCLUSION: The more severe genotypes worsened HRQoL in two domains of physical health (general health and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
2
23
0
1
Order By: Relevance
“…In Brazil, a report on 110 SCD patients found that one-third had depression, and this drove the HRQoL scores lower in this subgroup. 50 In a cohort of children and adolescent SCD patients, depression was also associated with worse HRQoL scores in all domains. 51 Depression was found to be associated with neurocognitive deficits in other patient populations.…”
Section: Discussionmentioning
confidence: 93%
“…In Brazil, a report on 110 SCD patients found that one-third had depression, and this drove the HRQoL scores lower in this subgroup. 50 In a cohort of children and adolescent SCD patients, depression was also associated with worse HRQoL scores in all domains. 51 Depression was found to be associated with neurocognitive deficits in other patient populations.…”
Section: Discussionmentioning
confidence: 93%
“…Socio-demographic and genotype aspects of study participants Among the 22 articles selected, the majority of the participants were: women in 21 (95.5%) (1)(2)(3)(4)(5)7,(13)(14)(15)(16)(17)(18)(20)(21)(22)(23)(24)(25)(26)(27)(28) , with HbSS / Sβº Tal genotypes in 19 (86.4%) (1)(2)(4)(5)7,(13)(14)(15)(16)(17)(19)(20)(22)(23)(24)(25)(26)(27)(28) ; unmarried children in 13 (59.1%) (1,(3)(4)(5)13,15,(20)(21)(22)(23)(24)…”
Section: Chart 1 (Concluded)mentioning
confidence: 99%
“…This review demonstrated that six HRQoL assessment scales were used, three generic and three specific. The generic ones were: Medical Outcome Study 36 item Short Form -SF36 (n = 11) (1,4,(13)(14)(16)(17)21,23,(26)(27)(28) ; World Health Organization Quality of Life Assessment Instrument Bref -WHOQOL-Bref (n = 7) (3,15,(19)(20)22,(24)(25) and EuroQol EQ-5D (n = 1) (18) .…”
Section: Scales Used To Assess Health-related Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations